2006
DOI: 10.1002/mame.200500385
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Structure of Constituent Fibres in Thermally Bonded Nonwovens

Abstract: Summary: A new process has been developed to produce three‐dimensional nonwovens directly from staple fibres. In order to establish suitable windows of the process parameters to achieve high‐quality nonwoven products, the effects of thermal bonding temperature, dwell time and mould material on the morphology and structure of the fibre have been investigated using PP/PET bi‐component fibres. It was evident from both scanning electron microscope images and Raman spectra that thermal‐induced shrinkage of the PP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…higher degree of chain orientation, have substantially higher tensile strength but lower elongation 10. As aforementioned, in the previous study,6 it was found that the birefringence of the PP sheath fiber was closely correlated with the degree of the thermal‐induced shrinkage, crystallinity and orientation factor after the thermal‐bonding process. Therefore, the birefringence values of the fibers in the different samples are also listed in Table 2 as a measure to explore the relationship between the properties of the constituent fiber and those of the fabrics.…”
Section: Experimental Partmentioning
confidence: 66%
See 4 more Smart Citations
“…higher degree of chain orientation, have substantially higher tensile strength but lower elongation 10. As aforementioned, in the previous study,6 it was found that the birefringence of the PP sheath fiber was closely correlated with the degree of the thermal‐induced shrinkage, crystallinity and orientation factor after the thermal‐bonding process. Therefore, the birefringence values of the fibers in the different samples are also listed in Table 2 as a measure to explore the relationship between the properties of the constituent fiber and those of the fabrics.…”
Section: Experimental Partmentioning
confidence: 66%
“…It is difficult to quantify the bonding features between the fibers, but it can be qualitatively seen that the bond between the fibers in the samples produced using a lower bonding temperature and/or shorter dwell time is weaker than that in the samples produced using a higher bonding temperature and/or longer dwell time, as shown in Figure 8. Therefore, although the higher birefringence shows that the fibers in the nonwoven samples produced using the shorter dwell time and lower bonding temperature have higher breaking force,6,10 the weak bonds between the fibers lead to the lower breaking force of the corresponding fabrics as shown in Figure 1, 2 and 5.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations